2000
DOI: 10.1139/t00-015
|View full text |Cite
|
Sign up to set email alerts
|

An equation to represent grain-size distribution

Abstract: The grain-size distribution is commonly used for soil classification; however, there is also potential to use the grain-size distribution as a basis for estimating soil behaviour. For example, much emphasis has recently been placed on the estimation of the soil-water characteristic curve. Many methods proposed in the literature use the grain-size distribution as a starting point to estimate the soil-water characteristic curve. Two mathematical forms are presented to represent grain-size distribution curves, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(99 citation statements)
references
References 15 publications
1
89
1
8
Order By: Relevance
“…Thus, it is concluded that accuracy of a model, doesn't always increase with over-parameterization. This result was different from Hwang (2004) one as well as Fredlund et al (2000), who reported that the performance of the Fredlund model would be All small letters are signs for significant difference at level 5 %. SD standard deviation, Ave average Fig.…”
Section: Clay Groupcontrasting
confidence: 67%
See 4 more Smart Citations
“…Thus, it is concluded that accuracy of a model, doesn't always increase with over-parameterization. This result was different from Hwang (2004) one as well as Fredlund et al (2000), who reported that the performance of the Fredlund model would be All small letters are signs for significant difference at level 5 %. SD standard deviation, Ave average Fig.…”
Section: Clay Groupcontrasting
confidence: 67%
“…So that, in Fig. 7, except sandy texture group, Fredlund model provided the best fitting ability in majority number of all soil samples and also, for loamy and clay texture groups, due to having further parameters than models that have fewer parameters such as lognormal likewise, the relative performance increased with increase of clay content (Fredlund et al 2000;Hwang 2004). Also, we can consider that Fredlund model is physical one.…”
Section: Sand Groupmentioning
confidence: 83%
See 3 more Smart Citations